2004
DOI: 10.1080/13607860410001649662
|View full text |Cite
|
Sign up to set email alerts
|

Activity and psychological well-being in older people

Abstract: Affective well-being and life satisfaction between the ages of 50 and 74 were investigated as a function of the frequency with which individuals undertook six types of activity, after control for potential confounding variables. Overall activity level (across all types) was significantly positively associated with both outcome variables. Activities in the Family and Social and in the Church and Charity domains were found to be important in this age-range, but other types of activity were less consistently asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
0
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 18 publications
6
67
0
8
Order By: Relevance
“…For example, a recent study of community-dwelling middle-aged and older adults found that those who engaged in more activities reported greater affective well-being and life satisfaction (Warr, Butcher, & Robertson, 2004). Another study found that individuals with major depressive disorder experienced a significant increase in positive affective states (i.e., positive well-being and vigor) following 30 minutes of aerobic physical exercise (Bartholomew, Morrison, & Ciccolo, 2005).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 97%
“…For example, a recent study of community-dwelling middle-aged and older adults found that those who engaged in more activities reported greater affective well-being and life satisfaction (Warr, Butcher, & Robertson, 2004). Another study found that individuals with major depressive disorder experienced a significant increase in positive affective states (i.e., positive well-being and vigor) following 30 minutes of aerobic physical exercise (Bartholomew, Morrison, & Ciccolo, 2005).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 97%
“…However, males and females may experience social interactions with family differently, and therefore, place different value on experiencing negative "family issues". Research has suggested that females' interaction with family and other groups (i.e., friends, community, groups) affects their well-being more so than males (Warr, Butcher, & Robertson, 2004). Further, in support of previous research, research has also suggested that female's survival rates increased with increases in social interactions while males survival rates was increased by solitary activities (Agahi & Parker, 2008).…”
Section: Analysis Of Dissertation Findingssupporting
confidence: 69%
“…Specifically, engaging in enjoyable and meaningful leisure activities can help in coping with stress and disabilities, decrease levels of depression and loneliness, reduce insomnia, improve the aging adjustment process, enhance social networking, prevent cognitive decline, and reduce the risk of dementia (Bennett, 2002;Dupuis, 2008;Endeshaw & Yoo, 2016;Mannell & Snelgrove, 2012;Scarmeas & Stern, 2003;Wang, Karp, Winblad, & Fratiglioni, 2002;Warr, Butcher, & Robertson, 2004).…”
Section: Leisure and Agingmentioning
confidence: 99%